STRATEGI PENGEMBANGAN TEKNOLOGI E-COMMERCE UMKM RUMAH SAYUR LEMBANG MENGGUNAKAN METODE ANALISIS SWOT - Bahtiar Gunawan; Maulana Shaleh Mubarak; Nisrina Anbar; Rangga Sanjaya (Universitas Islam Kuantan Singingi, 2020)
The research aims to identify the fundamental potential information of internal and external factors that determinant strategies that can be used in strategy development. The development of Micro, Small and Medium Enterprises (UMKM) Rumah Sayur impresses slowly, because of the missed in e-commerce technology in its business. Cause a lack of opportunities to be able to compete in the business world. There needs to be a system development strategy to run and develop well. One of the ways that can be done to help determine an e-commerce technology system development strategy is to conduct a SWOT analysis. SWOT analysis is necessary to know the strengths and weaknesses as well as opportunities and threats to the company or business to face strict competition as well as to give competitiveness among Micro, Small and Medium Enterprises (UMKM. And the results of the analysis describe the analysis of the internal business factors and the company's e-commerce technology system as well as the external factors of business and the SME's e-commerce technology system Rumah Sayur From the results of the analysis, it was concluded that Micro, Small and Medium Enterprises (UMKM) Rumah Sayur need to take policy aggressive strategy to develop e-commerce technology given the high strength and opportunity in the middle of existing Micro, Small and Medium Enterprises (UMKM) competition